Narratives Of Australian Aboriginals; Effects Of Its Stolen Generation (Journal of Pharmaceutical Negative Results, 2023)
The Australian Aboriginal community has been on the land for 70,000 years and the contribution goes from medicine to food. Even in architecture, the invasion not only took the land but also destroyed them. They have covered millions of plants and weed out the poisons. This migrated community changed the barren lands of Eden to liveable space, they had a peculiar way of having urban designs, planning of architectures and even the art in the public form. During 1788, post the war The British wanted to take over the land to build prisons and have the prisoners in the island. The population of Aboriginal's were more than 250,000 later the colonists killed many due to the unnamed disease and refused to treat them. This left only with less than 50,000, they removed the indigenous people of the land and even declined the citizenship rights, they were removed in mass numbers, converted and even kidnapped to be slaves. The purpose of this research is to bring out the hardships and misery gone through the community for several hundred years. These people own the land straight away; they have been evaded and their houses have been destroyed by the ones with heavy machinery. Australia’s first people were buried in the same land while their children were being slaved.